COMPARATIVE ANALYSIS OF MANAGEMENT OF HIGHER EDUCATION SYSTEMS IN FRANCE AND SPAIN (EDUCATION IN THE 21ST CENTURY, 2023)
Every developed country has its own higher education system, but almost all of them are built on the same principles. France and Spain are the countries distinguished by their characteristic features, which we present in this article. While reviewing the higher education systems of France and Spain, we have clearly shown the similarities and differences in the management, financing and structures of the higher education systems of these countries. The study revealed that the management of the education systems of France and Spain is carried out by the central management authority (in France by the Ministry of National Education, in Spain by the Ministry of Education, Science and Sport), autonomous regions and local authorities (university).The main features of the French higher education system are the predominance of state universities, free education for everyone, including foreigners, and practically the same quality of education in both the capital and the provinces. As a country with a strong tradition of centralization, France maintains an education system with dominant control of the state, which has the prerogative to define and implement a higher education policy.The peculiarities of higher education in Spain include: paid tuition, a high-quality and complex curriculum, an independent choice of academic policy by universities, high school graduation exams consideration (bachilerato) as entry exams for universities. The most important common feature for both countries is the principle of “academic freedom”, i.e. the student independently determines the list of subjects to study, combining the educational process with scientific research.Above we present tables on a comparative analysis of external and internal management, the financing systems in France and Spain, the structure of their higher education, as well as the assessment system and the requirements for admission to universities in these countries.
Keywords: Higher education, centralization, education authorities, financing, assessment, admission, education structure